Identification of financial and macroeconomic shocks in a VAR model of the Polish economy. A stability analysis - Ulrichs, Magdalena (Economics and Business Review, 2018)
Dynamic macroeconomic models (both VAR and DSGE) currently play a very significant role in macroeconomic modelling. But these types of models rarely take into account the impact of financial markets on the behaviour of economies, they are rather more focused on the monetary transmission mechanism. The financial crisis of 2007-2008 highlighted the impact of the financial market on the macroeconomy. In this context macroprudential policy and financial stability analysis has gained a stronger meaning. The main aim of the paper is to estimate a model that simultaneously explains the dynamics of macroeconomic and financial variables and to assess whether the identified relationships are stable over time. Therefore, based on the estimated empirical structural vector autoregression model explaining the interactions between the real economy, the financial system and monetary policy in Poland, financial and macroeconomic shocks were identified. It was shown that the impulse reaction functions changed after the financial crisis. On the basis of Markov‑ Switching vector autoregression model probabilities of transitions between states of the economy and the regime-dependent impulse reaction functions were estimated.